2017
DOI: 10.1021/acs.langmuir.7b02103
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous Sol–Gel Synthesis of Anatase Nanoparticles and Their Electrophoretic Deposition in Porous Alumina

Abstract: Titanium dioxide (TiO) nanoparticles were synthesized by nonaqueous sol-gel route using titanium tetrachloride and benzyl alcohol as the solvent. The obtained 4 nm-sized anatase nanocrystals were readily dispersible in various polar solvents allowing for simple preparation of colloidal dispersions in water, isopropyl alcohol, dimethyl sulfoxide, and ethanol. Results showed that dispersed nanoparticles have acidic properties and exhibit positive zeta-potential which is suitable for their deposition by cathodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…All spectra were corrected with reference to adventitious aliphatic carbon taken at 285.0 eV. Nanocrystalline anatase (TiO 2 obtained by solvothermal sol–gel) and ALD (amorphous) HfO 2 were used as references.…”
Section: Methodsmentioning
confidence: 99%
“…All spectra were corrected with reference to adventitious aliphatic carbon taken at 285.0 eV. Nanocrystalline anatase (TiO 2 obtained by solvothermal sol–gel) and ALD (amorphous) HfO 2 were used as references.…”
Section: Methodsmentioning
confidence: 99%
“…These membranes can be further used as templates, for micro-and nano-structuration of different materials highly demanded in the nanotechnology field. Several distinct morphologies from solid nanowires [26][27][28][29][30][31][32][33][34][35] , segmented nanowires of varying composition [36][37][38] or diameter 37,39 , hollowed tubular wires also referred to as nanotubes [40][41][42][43][44][45][46][47][48] , nanocones 49 , Y-branched wires [50][51][52][53][54][55][56] , to 3D networks of interconnected nanowires 26, 57-62 can be obtained by filling the previously generated porous structure. This can be achieved through different growth techniques such as electrochemical deposition, CVD, ADL, sputtering, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium has been used as an alkaline flow battery electrolyte when coordinated with catechol [57]; the stability of these compounds under electrochemical cycling indicated that a solid analogue might be used in a solid-electrode battery. Titanium isopropoxide has been used to synthesize TiO 2 nanoparticles by sol-gel synthesis [58], and was chosen as a titanium source due to the formation of isopropanol as a side product, which would boil in the high-temperature reaction mixture. These papers influenced the synthesis in this work by implying that multiple quinones may coordinate to metals either as bidentate or monodentate ligands, and by using titanium as a stable metal center for solid metal-organic materials.…”
Section: Resultsmentioning
confidence: 99%